Characterization of zinc oxide-based varistor ceramics prepared using solid state route and co-precipitation processing - Mohd Sabri Mohd Ghazali (Selangor: Universiti Putra Malaysia, 2014)
There were few reports of fabrication of varistor ceramics that used as a protective device for electrical equipments from transient voltage surges. using other method than conventional solid-state. Hence, it is useful to characterize in terms of morphology, electrical non-linearity characteristics, and optical properties of it prepared by using co-precipitation processing, as this produces fine and homogenous powder, as well as conventional solid-state route. The objectives of the study are; to prepare four systems of' ZnO based varistor ceramics through conventional solid-state route and co-precipitation technique to determine which factors affect most on electrical non-linearity behavior: secondly to carry out optical study of four systems of ZnO based varistor ceramics obtain from conventional solid-state route and co-precipitation technique to elucidate the structure arrangement; and thirdly to investigate the degradation behavior of one system of ZnO based varistor ceramics (ZnO-Bi203-Ti02) to ascertain which preparation technique produce most stable electrical non-linearity coefficient.